Diversities in timing of sexual debut among Nigerian youths aged 15-24 years: parametric and non-parametric survival analysis approach. (2017)
Objective: This study examined gender, generational, cultural and social diversities in timing of sexual debut among Nigerian youths and determined factors influencing the timings. Methods: We extracted data of respondents aged 15-24 years from 2012 Nigeria nationally representative data. The outcome of interest was time at sexual debut while predictors included residence, marital status, zones, education, religion, age at first marriage. Data was censored, cox proportional hazard and generalized gamma models were used to model age at sexual debut with p=0.05. Results: The median survival time of sexual debut was 19 years, female youths were twice as likely to begin sexual activities than their male counterparts, HR=1.99, 1.87-2.11 while uneducated youths were more than twice likely to have earlier sexual debut than those with higher education, HR=2.19, 1.95-2.25. Likelihood of having had sexual debut was about 30% higher among those aged 20-24 years than those aged 15-19 years, HR=1.27, 1.19-1.36. Conclusion: Females from poor households mostly in rural areas with no education and who married early in life were more likely to have earlier sexual debut. Both teenagers and young adults are on different trajectories of sexual debut but both urgently need sexual and reproductive health education to delay sexual debut.